Niclosamide, an antihelmintic drug, enhances efficacy of PD-1/PD-L1 immune checkpoint blockade in non-small cell lung cancer. Issue 1 (11th September 2019) - Luo, Fan; Luo, Min; Rong, Qi-Xiang; Zhang, Hong; Chen, Zhen; Wang, Fang; Zhao, Hong-Yun; Fu, Li-Wu
Abstract : Background: PD-1/PD-L1 blockade has received approval for clinical application due to its encouraging benefit with improving prognosis in selected populations. Unfortunately, the response to immunotherapy for many patients remains unsatisfactory. It remains a great challenge to generate potential combinations that will outperform single agents alone with regard to anti-tumor activity. Methods: Using NSCLC cell lines and mouse models, we explored the effects of combined niclosamide and PD-L1 blockade on tumor growth and T cell function. Furthermore, we investigated the relationship between PD-L1 and p-STAT3 expression in tumor samples from patients with NSCLC using IHC, as well as their relationship to patient survival. Results: In vitro, niclosamide, an antihelmintic drug, enhanced the cancer cell lysis mediated by T cells in the presence of PD-L1 blockade. Accordingly, mice treated with niclosamide and PD-L1 antibody showed significant delay in tumor growth and increased survival which were associated with the increase of tumor infiltrating T cells and granzyme B release. Importantly, we found niclosamide could decrease the expression of PD-L1 in both a concentration- and time-dependent manner in NSCLC cells, which was linked to the blockage of p-STAT3 binding to the promoter of PD-L1. Conclusions: An enhancement of PD-L1 antibody by niclosamide was observed in inhibition of NSCLC growth in vitro and in vivo, which was involved in blockage of p-STAT3 binding to promoter of PD-L1 and finally downregulation of PD-L1 expression. These encourage the combination therapy of niclosamide and PD-1/PD-L1 blockade to be further studied in clinic.